Discovery of hyperstable noncanonical plant-derived epidermal growth factor receptor agonist and analogs - Loo, Shining (2022)
Here, we report the discovery of the first plant- derived and noncanonical epidermal growth factor receptor (EGFR) agonist, the 36-residue bleogen pB1 from Pereskia bleo of the Cactaceae family. We show that bleogen pB1 is a low-affinity EGFR agonist using a suite of chemical, biochemical, cellular, and animal experiments which include incisor eruption and wound- healing mouse models. A focused positional scanning pB1 library of Ala- and D-amino acid scans yielded a high-affinity pB1 analog, [K29k]pB1, with a 60-fold-improved EGFR affinity and mitogenicity. We show that the potency of [K29k]pB1 and the epidermal growth factor (EGF) is comparable in a diabetic mouse wound-healing model. We also show that both bleogen pB1 and [K29k]pB1 are hyperstable, being >100-fold more stable than EGF against proteolytic degradation. Overall, our discovery of a noncanonical proteolytic-resistant EGFR agonist scaffold could open new avenues for developing wound healing and skin regeneration therapeutics and biomaterials.